Meta-analysis of the association between dietary inflammatory index and cognitive health - Ding, Tianze; Aimaiti, Maimaitiyusupu; Cui, Shishuang; Shen, Junhao; Lu, Mengjie; Wang, Lei; Bian, Dongsheng (Frontiers in Nutrition, 2023)
Background Some studies have shown that a pro-inflammatory diet may be associated with cognitive function, but their conclusions have varied considerably. We here present a meta-analysis of the current published literature on DII score and its association with cognitive health. Methods In this meta-analysis, the PubMed, Embase, Web of Science, and Cochrane databases were searched in Sep. 2022. The reported indexes, specifically OR, RR, and β, were extracted and analyzed using R version 3.1.0. Results A total of 636 studies in databases were identified, and 12 were included in the meta-analysis. Higher DII was associated with an increased risk of AD and MCI (OR = 1.34; 95% CI = 1.21-1.49). Meanwhile, it may also cause global function impairment (Categorical: OR = 1.63; 95% CI = 1.36-1.96) and verbal fluency impairment (Continuous: OR = 0.18; 95% IC = 0.08-0.42). But there was no significant association between DII and executive function (Categorical: OR = 1.12; 95% IC = 0.84-1.49; Continuous: OR = 0.48; 95% IC = 0.19-1.21) or episodic memory (Continuous: OR = 0.56; 95% IC = 0.30-1.03). Conclusion A pro-inflammatory diet is related to AD, MCI, and the functions of some cognitive domains (specifically global function and verbal fluency). However, the current evidence on the role of diet-induced inflammation in different cognitive domains should be supported by further studies in the future.